2014
DOI: 10.1109/jsee.2014.00115
|View full text |Cite
|
Sign up to set email alerts
|

Novel sensor selection strategy for LPI based on an improved IMMPF tracking method

Abstract: Sensor platforms with active sensing equipment such as radar may betray their existence, by emitting energy that will be intercepted by enemy surveillance sensors. The radar with less emission has more excellent performance of the low probability of intercept (LPI). In order to reduce the emission times of the radar, a novel sensor selection strategy based on an improved interacting multiple model particle lter (IMMPF) tracking method is presented. Firstly the IMMPF tracking method is improved by increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Technically speaking, low transmit power, short dwell time, large revisit interval, and ultra-low side lobe antenna will lead to better LPI performance. Thus, the problem of LPI based radar resource scheduling in traditional monostatic radars has been extensively studied from various perspectives [20][21][22][23][24][25][26] [26]. In [24], a novel radar energy control algorithm based on an improved interacting multiple model particle filtering (IMMPF) was formulated for LPI performance enhancement, which controlled the radiation time and power of radar according to the target's range and radar cross section (RCS) with a given probability of target detection.…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Technically speaking, low transmit power, short dwell time, large revisit interval, and ultra-low side lobe antenna will lead to better LPI performance. Thus, the problem of LPI based radar resource scheduling in traditional monostatic radars has been extensively studied from various perspectives [20][21][22][23][24][25][26] [26]. In [24], a novel radar energy control algorithm based on an improved interacting multiple model particle filtering (IMMPF) was formulated for LPI performance enhancement, which controlled the radiation time and power of radar according to the target's range and radar cross section (RCS) with a given probability of target detection.…”
Section: Background and Motivationmentioning
confidence: 99%
“…In [24], a novel radar energy control algorithm based on an improved interacting multiple model particle filtering (IMMPF) was formulated for LPI performance enhancement, which controlled the radiation time and power of radar according to the target's range and radar cross section (RCS) with a given probability of target detection. Later, Zhang et al [25] developed an optimal sensor selection strategy based on passive sensor cooperation, and it was shown that the proposed algorithm can decrease the radar radiation times with excellent target tracking accuracy. Chen et al extended the results of the previous research and presented a radar radiation control strategy for multiple aircraft platforms based on time difference of arrival (TDOA) cooperation [26], which utilized the comparison of covariance and the predefined threshold to control the radiation state [27].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Shi et al [17] proposed an LPI-based resource management algorithm for target tracking in a distributed radar network. Zhang et al [18] investigated a sensor selection strategy to reduce the emission times of the radar based on an improved interacting multiple model particle filter (IMMPF) tracking method. Generally, the above works provide us an opportunity to deal with the LPI optimization problem of a radar network system.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, extensive research has been conducted in LPI optimization from various perspectives [1528]. In [18], the authors propose an optimal sensor selection strategy based on passive sensor cooperation, where the results are extended in [20] and a time difference of arrival cooperation based radar radiation control in multiple aircraft platforms is proposed. Shi et al address the LPI optimization schemes in radar networks for the first time [21–24], and it has been demonstrated that radar network systems with multiple transmitters and multichannel receivers can provide significant LPI performance advantages over traditional monostatic radar systems.…”
Section: Introductionmentioning
confidence: 99%